Dualitas Peran Pemimpin Kristen Menavigasi Kepemimpinan Adat dan Tuntutan Organisasi Modern - Yan Rigel Para'pean; Imelda Toda; Lusiana Paembong; Ludiana Ludiana; Refania Tonglolangi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Christian leaders in Indonesia are often faced with a complex duality of roles, where they must navigate the demands of tradition-based and consensus-based customary leadership with modern organizational expectations that emphasize efficiency and formal procedures. This gap creates significant tension in leadership practice. This research aims to (1) theoretically analyze the points of tension and potential synergies between the two leadership models, and (2) synthesize a conceptual framework containing practical strategies to harmonize the two roles. The method used in this study is qualitative with a literature review approach, which in-depth analyzes various relevant academic sources. The results of the study show that the main tension lies in differences in authority bases, decision-making processes, and value priorities. As a solution, this study formulates a navigation framework that is based on the leader's mindset as a